Silicon oxide nanoparticles alleviate chromium toxicity in wheat (Triticum aestivum L.). (15th December 2022) - Manzoor, Natasha; Ali, Liaqat; Ahmed, Temoor; Rizwan, Muhammad; Ali, Shafaqat; Shahid, Muhammad Shafiq; Schulin, Rainer; Liu, Ying; Wang, Gang
Abstract: Increasing chromium (Cr) contamination in agricultural soils is a threat to crop yields and quality. Recently, nano-enabled strategies have been emerging with a great potential towards improving crop production and reclaiming the heavy metal contaminated soils. This study aimed to elucidate the potential of silicon oxide nanoparticles (SiONPs) on optimizing wheat growth and yield against Cr stress-induced phytotoxicity. Spherical crystalline SiONPs with the diameter in the range of 15–24 nm were applied at a dose of 250 mg kg −1 soil for pot experiments planted with wheat seedlings, with or without Cr contaminations. The pot experiment results showed that SiONPs amendments significantly improved the plant length (26.8%), fresh (28.5%) and dry weight (30.4%) as compared with the control treatment. In addition, SiONPs also enhanced photosynthetic activity, antioxidant enzyme contents (CAT, APX, SOD and POD content) and reduced the reactive oxygen species (ROS) in wheat plants under Cr stress condition. The alleviation of Cr toxicity was deemed to be associated with the reduced Cr uptake into the roots (−39.6%) and shoots (−35.7%). The ultrastructural analyses revealed that the application of SiONPs in Cr contaminated soils maintained the normal cellular structure of the wheat plant, as compared with those of controls without SiONPs. These results provide the first evidence showing the great potential of SiONPs application towards alleviating the Cr stress for optimized wheat growth and yield in Cr contaminated soils.